Thiocyanato-bridged platinum heterocycles: structure and properties of disc-like metallomesogens - Eran, BB; Singer, D; Pickardt, J; Praefcke, K (ELSEVIER SCIENCE SA, 2001)
The synthesis and liquid crystalline properties of novel disc-like di- and tetra-platinum organyls have been described recently. Here, the synthesis and mesomorphic properties of the first thiocyanato-bridged, sheet-shaped di- and tetra-platinum complexes are described. Structural features of these sheet-shaped thiocyanato-bridged di- and tetra-platinum organyls based on various methods (e.g. H-1-, C-13-, Pt-195-NMR) are discussed and related to the mesomorphic properties of these compounds. In addition, the molecular structure of a new thiocyanato-bridged diplatinum organyl carrying eight hexyl chains has been elucidated by single crystal X-ray diffraction analysis. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: cycloplatination; liquid crystals; metallomesogens; thiocyanato-bridged platinum organyls; X-ray structure analysis; ORTHOPALLADATED IMINE DERIVATIVES; TRANSFER INDUCED MESOPHASES; APOLAR ORGANIC-SOLVENTS; LIQUID-CRYSTALS; PALLADIUM ORGANYLS; PHASE-BEHAVIOR; COLUMNAR; COMPLEXES; Chemistry